Test-Case Generation for SQL Nested Queries with Existential Conditions - Caballero, Rafael; Luzon-Martin, José; Tenorio-Fornes, Antonio (Electronic Communications of the EASST, 2013)
This paper presents a test-case generator for SQL queries. Starting with a set of related SQL views that can include existential subqueries in the conditions, the technique finds a database instance that can be used as a test-case for the target view. The proposal reduces the problem of generating the test-cases to a Constraint Satisfaction Problem using finite domain constraints. In particular, we present a new approach for existential conditions that makes possible to find test-cases for a wider set of queries. The soundness and correctness of the technique with respect to a simple operational semantics for SQL queries without aggregates is proven. The theoretical ideas have been implemented in an available prototype.